PENGARUH CITRA MEREK AND BRAND EQUITY TERHADAP PURCHASE DECISION PIA DI CV. PIA MANALAGI PROBOLINGGO - Junaidi, Junaidi (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This research was conducted on CV. Pia Manalagi Probolinggo in order to see the effects of brand image and brand equity with the decision to purchase manalagi probolinggo. The approach of the study with quantitative descriptive with sample collection techniques based nonprobability sampling 100 with the number of respondents who buyers of reinsurance. The method of analysis based on data the validity and realibilitas test, classical assumption test, multiple linear analysis, analysis of determination (R2) and hypothesis testing (F test and t test). From the results of the activities carried out by obtained: (1) There was a positive and significant influence of brand image on purchasing decisions at CV. Pia Manalagi Probolinggo with an Fcount > Ftable (76.232 > 3.090) On the significantly by 0.000 < 0.05 While the value of tcount ? ttable (5.219 ? 1.985) (Sig. 0.000 ? 0.025). (2) Furthermore obtained the effects of brand equity where also contributed to show significance of the purchasing decisions with a value of Fcount > Ftable (76.232 > 3.090) with a significant level of 0.000 < 0.05 and a value of tcount ? ttable (4.100 ? 1.985) (Sig. 0.000 ? 0.025).